2020
DOI: 10.5171/2020.628159
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Emission Disclosure, Media Exposure, Environmental Performance, Characteristics of Companies: Evidence from Non Fincancial Sectors In Indonesia

Abstract: This paper is aiming to analyze the influence of media exposure, environmental performance, type of industry, company size, profitability and leverage on the carbon emission disclosure in non financial sectors in Indonesia. The carbon emission disclosure was measured by scoring a checklist of the carbon emission disclosure. The media exposure, environmental performance, type of industry, company size, profitability and leverage are the determinants of the carbon emission disclosure. This research used secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 0 publications
5
16
0
1
Order By: Relevance
“…Previous research conducted by Rahayu et al (2021) found that media exposure can significantly influence environmental disclosure. The same was found by Ulupui et al (2020) who stated that media exposure significantly influences corporate social responsibility (CSR) disclosure or carbon emission disclosure. Based on the explanation above, the following hypothesis is formulated: H 3 : Media exposure has a positive effect on carbon emissions accounting disclosures.…”
Section: Hypothesis Developmentsupporting
confidence: 60%
See 2 more Smart Citations
“…Previous research conducted by Rahayu et al (2021) found that media exposure can significantly influence environmental disclosure. The same was found by Ulupui et al (2020) who stated that media exposure significantly influences corporate social responsibility (CSR) disclosure or carbon emission disclosure. Based on the explanation above, the following hypothesis is formulated: H 3 : Media exposure has a positive effect on carbon emissions accounting disclosures.…”
Section: Hypothesis Developmentsupporting
confidence: 60%
“…Based on the study of Abdullah et al (2020) and also Ulupui et al (2020), the measurement of media exposure in this study is measured using a dummy variable where the company gets a value of 1 if it discloses information related to carbon emissions disclosure via the company website, or on other media such as online news portals, and a value of 0 otherwise.…”
Section: Media Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…As a result, more and more companies are actively providing carbon emission data on websites, in the form of annual reports and sustainability reports. Research conducted (Abdullah et al, 2020;Tavakolifar et al, 2021;Ulupui et al, 2020), states that increased disclosure of corporate carbon emissions, occurs when high media exposure addresses excessive carbon emissions. According to signaling theory, when a company increases the disclosure of reduced carbon emissions through media exposure, investors receive good signals in the form of information about the company's environmental performance.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…According to the results of the study (Nasih et al, 2019;Ulupui et al, 2020), media exposure and oversight of corporate policies can improve social and environmental performance. Thus, media exposure can make it easier for stakeholders to know environmental conditions and performance related to carbon emissions produced.…”
Section: Introductionmentioning
confidence: 99%